Interactions Between Natural Nuclear Reactors and Microbial Evolutionary Processes - Easttom, Chuck (Journal of Evolutionary Science, 2026)
The impact of ionizing radiation on genetic change is well established, yet the extent to which naturally occurring radiation fields have influenced evolutionary trajectories remains incompletely understood. This study examined correlations between microbial evolution and the radiation and geochemical environments associated with natural fission reactors, with emphasis on the Oklo–Bangombé system in present-day Gabon, Africa. The current paper compares plausible doserate regimes adjacent to reactor zones with published observations of radiationinduced phenotypes, geneexpression changes, and repair strategies in model organisms and complex biotas. This study further considers indirect mechanisms (e.g., water radiolysis, redox restructuring, tracemetal mobilization) by which natural reactors could have modulated ecological selection pressures over long timescales. The synthesis supports the plausibility of three interacting pathways: (i) increased mutation supply under low, chronic dose rates; (ii) selection in oxidantrich, redoxstratified niches; and (iii) metabolic subsidies (e.g., H₂) from radiolysis that support chemotrophic guilds. Although temporal–spatial associations exist between reactor activity and biological innovations preserved in Paleoproterozoic strata of Gabon, current evidence remains correlational rather than demonstrably causal. The study further outlines testable predictions and experimental designs capable of discriminating among these mechanisms.
Keywords: Natural nuclear reactors; Ionizing radiation; Microbial evolution; Geochemical environment